Bangladesh Development Update, October 2016 : Sustained Development Progress - World Bank (World Bank, Washington, DC, 2016)
This update introduces Bangladesh's new poverty numbers at $1.90 per capita per day in 2011 purchasing power parity (PPP) prices, followed by an account of recent economic development, the outlook, risks, and policy responses. The revised poverty rates are significantly lower, but follow the same downward historical trend seen when using the 2005 international extreme poverty line. Bangladesh can bring its extreme poverty rate down to nearly zero by 2030 either by accelerating GDP growth to 9 percent per year, or by maintaining its recent growth rate while taking steps to make growth more inclusive. Bangladesh is on track to sustaining its recent 6 plus percent growth in the near and medium-term, driven by exports and strong domestic demand. Security, financial and trade shocks are the main risks. The policy challenges are to boost productivity and private investment by reforming business regulations, addressing infrastructure and energy deficits and increasing the efficiency of financial intermediation. A special policy focus in this report is on introducing carbon taxation.